Multicenter evaluation of the GenomEra SARS-CoV-2 assay kit - Lång Mika; Allard Annika; Blomqvist Soile; Iranto Irmeli; Vuorinen Tytti; Tapio Antti-Heikki; Vainio Jiri (United States, 2025)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) first emerged in late 2019, and quickly spread to every continent causing the global coronavirus disease 2019 (COVID-19) pandemic. Fast propagation of the disease presented numerous challenges to the health care industry in general and especially placed enormous pressure on laboratory testing. Throughout the pandemic, reverse transcription-PCR (RT-PCR)-based nucleic acid amplification tests have been the primary technique to identify acute infections caused by SARS-CoV-2. Since the start of the pandemic, there has been a constantly growing need for accurate and fast tests to enable timely protective and isolation means, as well as rapid therapeutic interventions. Here we present an evaluation of the GenomEra test for SARS-CoV-2. Analytical and clinical performance was evaluated in a multicenter setting with specimens analyzed using standard-of-care (SOC) techniques. Analytical sensitivity was assessed from spiked respiratory swab samples collected into different viral transport media, and in the best performer eSwab, the limit of detection was found to be 239 IU/mL in a heat processed sample. The GenomEra SARS-CoV-2 Assay Kit did not show specificity/cross-reactivity issues with common micro-organisms or other substances commonly found in respiratory specimens when analyzed both in vitro and in silico. Finally, the clinical performance was assessed in comparison to SOC techniques used at four institutions. Based on the analysis of 274 clinical specimens, the positive agreement of the GenomEra SARS-CoV-2 Assay Kit was 90.7%, and the negative agreement was 100%. The GenomEra SARS-CoV-2 Assay Kit provided accurate detection of SARS-CoV-2 with a short turnaround time in under 90 min.